Summary: Climate-Smart Agriculture in the 2017 SAN Sustainable Agriculture Standard - Rainforest Alliance (2018)
Climate change fundamentally and increasingly affects agriculture. Warming, drought and extreme weather are already altering yields and quality of crops produced around the world. They also stand to impact water availability, nutritional value of foods, and food security and as such the livelihoods of natural resource dependent communities as a whole. The economic effects are already being felt by farmers and across global supply chains. Agricultural businesses identify climate change as a serious long-term risk in supply management. At the same time, agricultural land use systems all contribute to greenhouse gas (GHGs) emissions. Chemical fertilizers, manure and methane from livestock, wastewater and deforestation (converting forests to croplands or grazing lands) are all major emitters of GHGs. Globally, direct agricultural practices generate 10-12% of GHGs. Add to that deforestation, and agriculture accounts for 25% of global GHG emissions. But agriculture and cattle production can also be a force for greater adaptation and resilience in the face of climate change. Under the right conditions, agriculture provides a multitude of environmental services, such as carbon sequestration, watershed protection and biodiversity conservation, all of which contribute to climate resilience. Certain sustainable practices help farmers under pressure from climate change to adapt and keep producing and improving without resorting to harmful techniques, and help companies manage and reduce climate risks in their supply chains. “Climate-smart agriculture” is an approach to reorienting agricultural and cattle production to the new realities of climate change. It creates the technical, policy and investment conditions for achieving sustainable agricultural development and food security as climate change unfolds. It is composed of three main pillars: •sustainably increasing agricultural productivity and incomes; •adapting and building resilience to climate change; and •reducing and/or removing GHG emissions where possible.